Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 7 - Algebraic Fractions - Chapters 1-7 Cumulative Review Problem Set - Page 324: 4



Work Step by Step

We evaluate the expression by substituting $a=0.4$ and $b=0.6$ throughout the expression and simplifying: $ab+b^{2}$ =$(0.4)(0.6)+(0.6)^{2}$ =$(\frac{4}{10})(\frac{6}{10})+(\frac{6}{10})^{2}$ =$(\frac{4\times6}{10\times10})+(\frac{6^{2}}{10^{2}})$ =$(\frac{24}{100})+(\frac{36}{100})$ =$(\frac{24+36}{100})$ =$(\frac{60}{100})$ =$0.6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.